Comparing Common Programming Languages to Parse Big XML File in Terms of Executing Time, Memory Usage, CPU Consumption and Line Number on Two Platforms - Abdo, Ahmed Mahdee; Alali, Sardar Hasan (European Scientific Journal, ESJ, 2016)
XML files are used widely to save the information especially in the field of bioinformatics about the whole genome. There are many programming languages and modules used to parse XML files in different platforms such as Linux, Macintosh and Windows. The aim of this report is to reveal and determine which common programming language to use and on which platform is better to parse XML files in terms of memory usage, CPU time consumption and executing time.